2023
DOI: 10.3390/diagnostics13030414
|View full text |Cite
|
Sign up to set email alerts
|

Developments and Performance of Artificial Intelligence Models Designed for Application in Endodontics: A Systematic Review

Abstract: Technological advancements in health sciences have led to enormous developments in artificial intelligence (AI) models designed for application in health sectors. This article aimed at reporting on the application and performances of AI models that have been designed for application in endodontics. Renowned online databases, primarily PubMed, Scopus, Web of Science, Embase, and Cochrane and secondarily Google Scholar and the Saudi Digital Library, were accessed for articles relevant to the research question th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 80 publications
0
23
1
Order By: Relevance
“…The switch to online and those that were originally not designed for online delivery resulted in increased psychological distress among students [ 2 ]. Majority of the respondents were females (79.4%, 55.6%, 65%, 54.1%) in previous studies [ 2 , 16 , 17 ], whereas, in our present study males (56.2%) were in majority than females (43.8%). Majority (25.7 %) stayed at home with family, similar to the present study (34.3%).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The switch to online and those that were originally not designed for online delivery resulted in increased psychological distress among students [ 2 ]. Majority of the respondents were females (79.4%, 55.6%, 65%, 54.1%) in previous studies [ 2 , 16 , 17 ], whereas, in our present study males (56.2%) were in majority than females (43.8%). Majority (25.7 %) stayed at home with family, similar to the present study (34.3%).…”
Section: Discussioncontrasting
confidence: 71%
“…Those stayed with families reported high levels of anxiety than others in these studies, which contradicts the present study, in which anxiety scores were high among those students who stayed with their friends. Studies in Saudi Arabia [ 17 ] reported depression, anxiety, and fear among dental interns. Accommodation, marital status and gender did not influence the psychological health of the participants which contradicts the present study in which females reported increased levels of depression, anxiety and stress than males and accommodation of students with their friends caused more anxiety than others.…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of DL, it has been suggested for various applications in the field of oral and dental health, such as tooth classification, detection and segmentation [ 9 , 10 ], endodontic treatment and diagnosis [ 11 ], periodontal problem tooth [ 12 ] and oral lesion pathology detection [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dental medicine has also started to benefit from such deep learning techniques [ 8 ]. Specifically, these techniques have been applied to panoramic radiographs and cone-beam computed tomography (CBCT) images with the aim of assisting clinicians in detecting and analyzing dental conditions and diseases in the maxillofacial region [ 9 , 10 , 11 ]. Examples include the detection of maxillary sinus mucosa [ 12 ], pharyngeal airway space [ 13 ], calcifications of the cervical carotid artery [ 14 ], jaw cysts [ 15 , 16 ], supernumerary mesio-buccal root canals on maxillary molars [ 17 ], vertical root fractures [ 18 ], and periapical lesions (PALs).…”
Section: Introductionmentioning
confidence: 99%